HUBUNGAN STATUS GIZI DENGAN SINDROM PRE MENSTRUASI PADA REMAJA PUTRI DI SMA FRATER DON BOSCO MANADO - Namsa, Apriliana Maria; Palandeng, Henry; Kallo, Vandri D (Universitas Sam Ratulangi, 2015)
Abstract : Pre Menstrual Syndrome is a collection of physical symptoms, psychological and emotional associated with a woman's menstrual cycle. The symptoms are expected and usually occur regularly on a two-week period before menstruation. The aim of research to determine the relationship of nutritional status with pre menstrual syndrome in young women at Frater Don Bosco Senior High School Manado. Design research is an analytic survey with cross sectional approach. This research was conducted in Frater Don Bosco Senior High School Manado on June 1th – 19th 2015. The sample in this research is purposive sampling with 60 respondents were included in the inclusion criteria. The instrument that uses questionnaires and observation sheets. The results of the statistical test using computerized systems by using the chi-square test (X2) at the level of significance 95% (α = 0,05). Statistical analysis showed p value = 0,000 with level of significance <0,05. Conclusion there is a meaningful correlation between nutritional status and pre menstrual syndrome in young women at Frater Don Bosco Senior High School Manado. Advice for young women to better maintain the nutritional status to reduce the risk of having symptoms of pre-menstrual syndrome heavier that can interfere daily activities. Keywords : Nutritional Status, Pre Menstrual Syndrome, Young Women Abstrak : Sindrom Pre Menstruasi adalah adalah kumpulan gejala fisik, psikologis dan emosional yang terkait dengan siklus menstruasi wanita. Gejala tersebut dapat diperkirakan dan biasanya terjadi secara reguler pada dua minggu periode sebelum menstruasi. Tujuan penelitian untuk mengetahui hubungan status gizi dengan sindrom pre menstruasi pada remaja putri di SMA Frater Don Bosco Manado. Desain penelitian survei analitik dengan pendekatan cross sectional. Penelitian ini dilakukan di SMA Frater Don Bosco Manado pada tanggal 1 Juni 2015 – 19 Juni 2015. Sampel dalam penelitian ini adalah purposive sampling dengan 60 responden yang memenuhi kriteria inklusi. Instrumen penelitian yaitu menggunakan kuesioner dan lembar observasi. Hasil penelitian uji statistik menggunakan sistem komputerisasi dengan menggunakan uji chi-square (X2) pada tingkat kemaknaan 95% (α = 0,05). Hasil uji statistik menunjukkan p value = 0,000 dengan level of significance < 0,05. Kesimpulan ada hubungan yang bermakna antara status gizi dengan sindrom pre menstruasi pada remaja putri di SMA Frater Don Bosco Manado. Saran untuk remaja putri agar lebih menjaga status gizi agar dapat mengurangi resiko mengalami gejala sindrom pre menstruasi yang lebih berat yang dapat mengganggu aktivitas sehari-hari. Kata kunci : Status Gizi, Sindrom Pre Menstruasi, Remaja Putri